7th war loan: now.. all together. - Beall, C. C. (Cecil Calvert), 1892-1967 (artist):::Creator::::::::::::; Rosenthal, Joe, 1911-2006 (photographer):::Contributor:::::::::::: (United States Government Printing Office)
U.S. Marines raising the American flag at Iwo Jima, Japan. The painting by C. C. Beall is based on a Pulitzer Prize-winning photograph taken by Associated Press photographer, Joe Rosenthal, of the second American flag raising by U.S. Marines on Mount Suribachi, Iwo Jima on February 23, 1945.